Respuesta :

Answer:

g(x) = x+3.

Step-by-step explanation:

i hope this helps :D

When a function is shrunk vertically, the function has undergone a form of transformation.

The resulting function when [tex]f(x) = 2x + 6[/tex] vertically shrink by 1/2 is [tex]f'(x) = x + 3[/tex]

Given that:

[tex]f(x) = 2x + 6[/tex]

[tex]k = \frac 12[/tex] --- shrink factor

When a function is shrunk vertically, the rule of transformation is:

[tex](x,y) \to (x,ky)[/tex]

So, we have:

[tex]f'(x) = k f(x)[/tex]

The new function becomes

[tex]f'(x) = \frac 12 \times (2x + 6)[/tex]

[tex]f'(x) = x + 3[/tex]

Hence, when [tex]f(x) = 2x + 6[/tex] is vertically shrunk by 1/2, the new function is [tex]f'(x) = x + 3[/tex]

Read more about transformations at:

https://brainly.com/question/11709244

ACCESS MORE